ANALYSIS OF THE EFFECTIVENESS OF DOLLYO CHAGI AND YEOP CHAGI KICK PANIPAK WONGPATTANAKIT IN THE GRAND PRIX TAEWONDO MATCH: ANALISIS EFEKTIVITAS TENDANGAN DOLLYO CHAGI DAN YEOP CHAGI PANIPAK WONGPATTANAKIT DALAM PERTANDINGAN GRAND PRIX TAEWONDO - Sefti Nurul Aini; Ach Zayul Mustain; Puji Setyaningsih (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The dollyo chagi kick can be done with 2 hits, namely the chest or stomach called momtong and the head direction called eolgol. The dollyo chagi kick that targets the head has relatively high points compared to those that hit the stomach and chest (Amdan & Sepdanius, 2019). The basic technique of the yeop chagi kick is a very effective kick technique to start an attack or defend against enemy attacks because it is easy to implement with a pushing technique. In this study, Kinovea 9.5 software was used to analyze the Dollyo Chagi and Yeop Chagi kicks of Panipak Wongpattanakit athletes. Data collection by preparing videos from world taekwondo youtube channels. The videos studied used the entire number of athlete matches, consisting of 4 matches, namely round of 16, quarterfinals, semifinals, and finals. The duration of the match consists of 2x3, namely each round has a time of 2 minutes and in 1 match there are 3 rounds. Based on the research results, it was concluded that the dollyo chagi kick was more effective than the yeop chagi kick, the yeop chagi kick was the second most effective kick after the dollyo chagi. Taekwondo, kick, analysis